2023
DOI: 10.1094/pdis-05-22-1236-re
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Prevalence of Seedborne Botrytis spp. in Dry Pea, Lentil, and Chickpea in Montana

Abstract: Botrytis spp. cause gray mold and are significant pathogens of pulse crops (dry pea, lentil, and chickpea). Seedling infection can result in plant stunting and death. In this study, 100 Botrytis isolates were recovered from pulse crop seed samples that were submitted to the Regional Pulse Crop Diagnostic Laboratory at Montana State University. Nine Botrytis species were found to be associated with pulse seeds in Montana based on a combination of cultural characteristics, the amplification of partial sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Recent studies have shown the ability of the lesser known Botrytis species to infect different legumes in vitro. B. euroamericana was able to infect chickpea, field pea, lentil and faba bean leaves during pathogenicity tests in vitro at the same rate as B. cinerea (Moparthi et al, 2023). B. caroliniana, B. pyriformis, B. aclada and B. paeoniae formed lesions on faba bean leaves in vitro, but have not been isolated from field-grown faba bean Garfinkel et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…Recent studies have shown the ability of the lesser known Botrytis species to infect different legumes in vitro. B. euroamericana was able to infect chickpea, field pea, lentil and faba bean leaves during pathogenicity tests in vitro at the same rate as B. cinerea (Moparthi et al, 2023). B. caroliniana, B. pyriformis, B. aclada and B. paeoniae formed lesions on faba bean leaves in vitro, but have not been isolated from field-grown faba bean Garfinkel et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…These large collections of studies provide the ability to conduct a meta‐analysis of the factors influencing B. cinerea's extensive genetic diversity. To summarize findings of these studies, we performed a meta‐analysis by compiling the publicly available data for >10,000 strains across 58 publications (Abdel Wahab, 2015; Acosta Morel et al., 2018; Albertini & Leroux, 2004; Albertini et al., 2002; Aliaga, 2013; Amiri et al., 2018; Asadollahi et al., 2013; Beever & Parkes, 1993; Ben Ahmed & Hamada, 2005; Campia, 2014; Cettul et al., 2008; Ciliberti et al., 2016; DeLong et al., 2020; Diao et al., 2019; Emilda, 2015; Esterio et al., 2011; Fan et al., 2015; Fekete et al., 2012; Fournier et al., 2005, 2013; Giraud et al., 1997; Giraud et al., 1999; Hu et al., 2018; Isenegger et al., 2008; Johnston et al., 2013; Kecskeméti et al., 2014; Kumari et al., 2014; Kuzmanovska et al., 2012; Leyronas et al., 2014; Lorenzini & Zapparoli, 2014; Ma & Michailides, 2005; Makris et al., 2022; Martinez et al., 2003; Mercier et al., 2019; Moparthi et al., 2023; Muñoz & Campos, 2013; Muñoz et al., 2002, 2016; Naegele et al., 2021; Pei et al., 2019; Polat et al., 2018; Rajaguru & Shaw, 2010; Román Ramos, 2013; Tanović et al., 2009, 2014; Testempasis et al., 2020; Toffolatti et al., 2020; Topolovec‐Pintarić et al., 2004; Törün & Biyik, 2022; Vaczy et al., 2008; Vatsa‐Portugal et al., 2014; Vercesi et al., 2014…”
Section: Extensive Genetic Diversity Of B Cinereamentioning
confidence: 99%
“…Recent studies have shown the ability of the lesser known Botrytis species to infect different legumes in vitro . B. euroamericana was able to infect chickpea, field pea, lentil and faba bean leaves during pathogenicity tests in vitro at the same rate as B. cinerea ( Moparthi et al., 2023 ). B. caroliniana , B. pyriformis , B. aclada and B. paeoniae formed lesions on faba bean leaves in vitro , but have not been isolated from field-grown faba bean ( Li et al., 2012 ; Zhang et al., 2016 ; Garfinkel et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%